2021
DOI: 10.1016/j.heliyon.2021.e06893
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whole-body vibration on wound healing in a mouse pressure ulcer model

Abstract: Background: Pressure ulcers are one of the most common complications of immobility resulting from pressure and shear. Whole-body vibration (WBV) has been shown to increase skin blood flow but little information is known about its effect on pressure ulcers. This study investigated the effects of WBV on wound healing in a mouse pressure ulcer model. Methods: Two cycles of ischemia-reperfusion were performed by external application of two magnetic plates to dorsal skin to induce stage II pressure ulcers character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Preclinical studies have shown that WBV may stimulate different brain regions and promotes the synthesis of neurotransmitters ( Ariizumi and Okada, 1985 ; Zhao et al, 2014 ; Heesterbeek et al, 2017 ) and neurotrophic factors ( Huang et al, 2018 ; Raval et al, 2018 ), alleviates (neuro)inflammation ( Peng et al, 2021 ; Chen et al, 2022 ; Oroszi et al, 2022a ); and improves cognitive functions ( Keijser et al, 2017 ; Boerema et al, 2018 ). Additionally, WBV may improve wound healing ( Weinheimer-Haus et al, 2014 ; Wano et al, 2021 ). Taken together, we hypothesize that WBV could provide a safe and low-cost alternative for active exercise during the early phase of postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have shown that WBV may stimulate different brain regions and promotes the synthesis of neurotransmitters ( Ariizumi and Okada, 1985 ; Zhao et al, 2014 ; Heesterbeek et al, 2017 ) and neurotrophic factors ( Huang et al, 2018 ; Raval et al, 2018 ), alleviates (neuro)inflammation ( Peng et al, 2021 ; Chen et al, 2022 ; Oroszi et al, 2022a ); and improves cognitive functions ( Keijser et al, 2017 ; Boerema et al, 2018 ). Additionally, WBV may improve wound healing ( Weinheimer-Haus et al, 2014 ; Wano et al, 2021 ). Taken together, we hypothesize that WBV could provide a safe and low-cost alternative for active exercise during the early phase of postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro trials have shown that vibrations exert anabolic effects on skeletal metabolism by promoting osteogenic activity, accelerating fracture and wound healing, preventing disuse atrophy in musculoskeletal tissues, improving the bone structure and muscle performance in a variety of different patient groups and could enhance chondrogenic differentiation of human adipose-derived mesenchymal stem cells [ 14 , 15 , 16 , 17 , 70 ]. Vibration has promising applications in many various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-body vibration (WBV) at 45 Hz seems to be promising in this regard. This treatment decreased neutrophil infiltration, and TNF-α levels enhanced collagen deposition in wounds and increased angiogenesis [ 17 , 18 ]. The combination of thermal images and vibration leads to preulcerative lesions in the diabetic foot [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For human patients, vibration intervention has been employed in medical rehabilitation, neurology, physiotherapy, and orthopedic surgery. In recent years, however, there has been an increase in vibration therapy research for other clinical applications, especially in wound and ulcer healing [29][30][31][32][33][34]. In [32], it is shown that vibration helps the healing of Stage I pressure ulcers in elderly patients.…”
Section: Introductionmentioning
confidence: 99%